Figures 32-39 from: Fritzén N (2011) On a new Dictyna species (Araneae, Dictynidae) from the northern Palaearctic confused with the East Siberian D. schmidti Kulczyński, 1926. ZooKeys 138: 93-108. https://doi.org/10.3897/zookeys.138.1849 - Marusik, Yuri; Fritzén, Niclas (Zenodo, 2011)
Figures 32-39 - Epigyne of Dictyna palmgreni sp. n. 32–33 from Pallastunturi and Dictyna major 34–39 from Pyhtää 32, 34, 36, 38 macerated epigyne, ventral 33, 35, 39 macerated epigyne, dorsal 37 macerated epigyne showing sac-like structure, frontal. Sac-like structure on Fig. 39 collapsed and sclerotised parts of epigyne became closer.